2006
DOI: 10.1111/j.1399-6576.2006.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory properties of local anesthetics and their present and potential clinical implications

Abstract: Development of new local anesthetic agents has been focused on the potency of their nerve-blocking effects, duration of action and safety and has resulted in a substantial number of agents in clinical use. It is well established and well documented that the nerve blocking effects of local anesthetics are secondary to their interaction with the Na+ channels thereby blocking nerve membrane excitability and the generation of action potentials. Accumulating data suggest however that local anesthetics also possess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
286
1
34

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(340 citation statements)
references
References 210 publications
(250 reference statements)
3
286
1
34
Order By: Relevance
“…It attenuates the formation of reactive oxygen metabolites [133], and the release of leukotrienes, , and histamine [135]. Similar effects have been demonstrated with bupivacaine and ropivacaine [130,131,136,137].…”
Section: Local Anestheticssupporting
confidence: 53%
See 2 more Smart Citations
“…It attenuates the formation of reactive oxygen metabolites [133], and the release of leukotrienes, , and histamine [135]. Similar effects have been demonstrated with bupivacaine and ropivacaine [130,131,136,137].…”
Section: Local Anestheticssupporting
confidence: 53%
“…It attenuates the formation of reactive oxygen metabolites [133], and the release of leukotrienes, , and histamine [135]. Similar effects have been demonstrated with bupivacaine and ropivacaine [130,131,136,137].Lidocaine also inhibits interferon-inducible IL-10 secretion in intestinal epithelial cells [138], attenuates IL-1β, IL -6, IL-8 and ICAM-1 on activated human umbilical vein endothelial cells [139], and impairs the secretions of IL-2, TNF-α, . Furthermore, in animals with LPS-induced lung injury, lidocaine attenuates the release of , whereas ropivacaine reduces the expression of ICAM-1 and the leukocyte adhesion [142].…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Several publications reported a broad range of anti-inflammatory actions of local anesthetics through their effects on the cells of the immune system as well as platelets, erythrocytes, and the microorganism itself 5 . Indeed, such agents have been utilized in the treatment of several conditions linked to inflammatory processes like interstitial cystitis, ulcerative proctitis, arthritis, herpetic infections and burns 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Further research has suggested that the mechanism of action may in part be associated with N-methyl-D-aspartate receptor antagonism (10). Other basic science papers suggest the inhibition of G-protein-coupled receptors and the inflammatory response as possible contributors to the analgesia seen with lidocaine infusions (11). Lidocaine infusion may also reduce anesthetic requirements and MAC by 20% to 40% (12,13), with potential economic benefits.…”
Section: Discussionmentioning
confidence: 99%